1D Metal Oxide Semiconductor Materials for Chemiresistive Gas Sensors: A Review. (2nd July 2021) - Yang, Bingxin; Myung, Nosang V.; Tran, Thien‐Toan
Abstract: While numerous types of gas sensors have been developed for various industries and applications such as the automotive industry, environmental monitoring, and personal safety, nanoscale chemiresistive gas sensors have gained significant research interest due to several advantages such as high sensitivity, low power consumption, and portability. An essential component of these gas sensors is the sensing material where metal oxide semiconductor (MOS) materials are the most prevalent sensing material. Since the adoption of nanoscale synthesis methods for sensing materials development, such as electrospinning and hydrothermal synthesis, many novel 1D MOS‐based nanostructured sensing materials have been demonstrated to enhance gas sensing performance. Overall, nanoengineering approaches and mechanisms for enhancement of gas sensing performance of 1D metal oxide‐based sensing materials are systematically discussed and categorized into several overarching strategies, such as tuning of materials dimension, morphology, and composition. Furthermore, integration of 1D sensing nanomaterials into sensor devices are discussed from the perspective of different chemiresistive sensor architectures and device fabrication methods. Finally, this review also discusses use of 1D MOS materials for emerging and novel electronic nose applications. Abstract : This is a systematic review of recent works demonstrating strategies to modulate and enhance sensing properties of chemiresistive gas sensors and sensor arrays (i.e., electronic nose) via nanoengineering compositions and morphologies of 1D metal oxide semiconducting sensing materials, such as, introduction of dopants and heterojunctions, complex hierarchical structures (e.g., core‐shell and branched structures), and manipulation of diameter and grain size/crystallinity.